2010
DOI: 10.5194/hess-14-2429-2010
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic design rainfall generator based on copulas and mass curves

Abstract: Abstract. The use of design storms can be very useful in many hydrological and hydraulic practices. In this study, the concept of a copula-based secondary return period in combination with the concept of mass curves is used to generate point-scale design storms. The analysis is based on storms selected from the 105 year rainfall time series with a 10 min resolution, measured at Uccle, Belgium. In first instance, bivariate copulas and secondary return periods are explained, together with a focus on which couple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…3 illustrates the 10 and 90 % percentile curves of the second-quartile autumn storms. Vandenberghe et al (2010a) showed that these curves are independent of the extremity of the storm. different copula families could be used to describe the dependences between the different variables (see Vandenberghe et al, 2010b).…”
Section: Historical Time Series Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…3 illustrates the 10 and 90 % percentile curves of the second-quartile autumn storms. Vandenberghe et al (2010a) showed that these curves are independent of the extremity of the storm. different copula families could be used to describe the dependences between the different variables (see Vandenberghe et al, 2010b).…”
Section: Historical Time Series Characteristicsmentioning
confidence: 99%
“…Based on the historical time series, it was observed that the increment in cumulative storm depth between two subsequent time instants in a Huff curve is not uniformly distributed (this observation was neglected in Vandenberghe et al, 2010a). Smaller increments occur more often than large increments.…”
Section: The Intrastorm-generating Submodel: Disaggregation Of Rectanmentioning
confidence: 99%
See 3 more Smart Citations